Reducing consumer materialism and compulsive buying through emotional intelligence training amongst Lithuanian students - Lekavičienė, Rosita; Antinienė, Dalia; Nikou, Shahrokh; Rūtelionė, Aušra; Šeinauskienė, Beata; Vaičiukynaitė, Eglė (Frontiers in Psychology, 2022)
Consumers’ inclinations towards materialism and compulsive buying are influenced by a variety of factors. Materialistic consumers face maladies that cause stress and lower subjective well-being and are unable to control their buying behaviour that in turn leads to social and financial issues. This paper aims to investigate the effect of emotional intelligence training on consumers’ materialism and compulsive buying. The experimental design involves 36 respondents across both groups. Findings confirm the hypothesis that ability-based training programmes can help consumers improve their emotional intelligence while also lowering their levels of materialism and compulsive buying. In sum, the results extend the existing literature on consumer materialism by providing an explanation on how specific emotional ability-based training can diminish materialistic and excessive buying inclinations. The development of emotional intelligence skills-based training programmes contributes to more sustainable consumer behaviour, mitigating the vulnerability to materialism and related addictive behavioural consequences.